Asuhan Keperawatan Gerontik Pada Pasien Kolesterol Dengan Pemberian Intervensi Jus Jambu Biji Merah Untuk Menurunkan Kadar Kolesterol Di Panti Werdha Kasih Ayah Bunda Tangerang - Indah Fitriyani; Siti Robeatul Adawiyah; Rina Puspita Sari; Siti Rahayu (Jurnal Ilmiah Kedokteran dan Kesehatan, 2023)
Background: Cholesterol is a condition where the amount of blood cholesterol exceeds normal limits. Cholesterol is one of the indicators in blood vessels and is a top priority in the management of health problems in developed and developing countries. The cause of cholesterol is unhealthy food intake, such as consuming high fat, low fruit and vegetable consumption, obesity, low physical activity, hypertension, stress, smoking, and alcohol use. Purpose: The purpose of this paper is to provide an overview of nursing care for cholesterol patients in lowering cholesterol levels by administering red guava juice. Method: Case study design using nursing care. This case study sample used 1 patient who was intervened for 7 days. Results: based on the results of implementation on Ny. M with the application of guava juice for 7 days obtained data on cholesterol levels in Ny. M on the third day decreased from 288 mg/dl to 199 mg/dl and cholesterol levels on the 7th day 190 mg/dl. So that the diagnosis of acute pain is resolved and it can be concluded that there is a change, this shows the effect of giving guava juice in lowering cholesterol levels